Polymerase Chain Reaction and Goldmann-Witmer Coefficient to Examine the Role of Epstein-Barr Virus in Uveitis. (2nd January 2019) - Smit, Derrick; Meyer, David; Maritz, Jean; de Groot-Mijnes, Jolanda D.F.
ABSTRACT: Purpose : To use polymerase chain reaction (PCR) and Goldmann-Witmer Coefficient (GWC) calculation to search for evidence that Epstein-Barr virus (EBV) causes uveitis. Methods : A prospective cross-sectional study where participants with positive multiplex EBV PCR results were further investigated by: 1) real-time PCR for EBV viral loads (VL) and 2) EBV GWC. Results : Eleven of 106 consecutive uveitis patients (10.4%) had positive multiplex PCR for EBV on aqueous humor sampling and 7/11 (63.6%) were HIV-positive. Only 4/10 (40%) cases had detectable intraocular EBV VLs which were always lower than the blood or plasma VL. EBV GWC was negative in all 10 cases tested. In 9/11 (81.8%) of these cases an alternative, more plausible cause of uveitis was identified. Conclusion : We found no evidence of active intraocular replication or antibody production to prove that EBV caused uveitis in these cases. In most cases an alternative treatable cause of uveitis was identified.